KAJIAN PENGEMBANGAN KOMODITAS PERIKANAN TANGKAP UNGGULAN DI GUGUS PULAU VIII PROVINSI MALUKU - Ayal, Frederik Willem (Departement of Aquatic Resources Management, Fisheries and Marine Science Faculty, Pattimura University, 2018)
Determination of leading commodities of capture fisheries is important for the direction of the development of Maluku Province, especially in the Island Group VIII of the Kei Islands. This cluster has large enough potential for capture fisheries but it is not be able to improve the welfare of local communities. This research was conducted with the aim of (1) determining the leading commodities of capture fisheries; (2) determine the appropriate fishing technology and; (3) reviewing the financial of leading commodities of capture fisheries. Data was collected by using fisheries socio-economic data collection methods that included observation, interviews and literature review. To determine leading commodities of capture fisheries and appropriate fishing technology in Cluster VIII were analyzed by using the Scoring Method, whereas to measure the business financial of leading commodities of capture fisheries using Business Feasibility Analysis Method. The results showed that the leading commodities of capture fisheries that could be developed in the Island Group VIII of the Kei Islands were grouper fish, tuna fish, anchovy, skipjack fish, emperor fish and yellow tail fish. Appropriate fishing technology that can be developed in the Island Group VIII of the Kei Islands, namely Mini Purse Seine, Drifting Gill Nets, Encircling Gill Nets and Ulur Fishing Rods. The business of superior capture fisheries commodities in Group VIII of the Kei Islands is financially feasible. ABSTRAK Penentuan komoditas perikanan tangkap unggulan menjadi penting bagi arah pembangunan Provinsi Maluku, khususnya di Gugus Pulau VIII Kepulauan Kei, mengingat potensi perikanan tangkap yang cukup besar belum bisa meningkatkan kesejahteraan masyarakat setempat. Penelitian ini bertujuan yaitu (1) menentukan komoditas perikanan tangkap unggulan; (2) menentukan teknologi penangkapan ikan tepat guna dan; (3) mengkaji kelayakan usaha komoditas perikanan tangkap unggulan. Pengumpulan data penelitian dilakukan menggunakan metode pengambilan data sosial ekonomi perikanan yang meliputi kegiatan observasi, wawancara dan kajian pustaka. Penentuan komoditas perikanan tangkap unggulan dan teknologi penangkapan ikan tepat guna pada Gugus Pulau VIII dianalisis menggunakan Metode Skoring, sedangkan pengukuran kelayakan usaha komoditas unggulan perikanan tangkap digunakan Metode Analisis Kelayakan Usaha. Hasil penelitian menunjukkan bahwa komoditas perikanan tangkap unggulan yang dapat dikembangkan di Gugus Pulau VIII Kepulauan Kei yaitu Ikan Kerapu, Ikan Tongkol, Ikan Teri, Ikan Cakalang, Ikan Lencam/Sikuda dan Ikan Ekor Kuning. Teknologi penangkapan ikan tepat guna yang dapat dikembangkan di Gugus Pulau VIII Kepulauan Kei yaitu Mini Purse Siene, Jaring Insang Hanyut, Jaring Insang Lingkar dan Pancing Ulur. Usaha komoditas perikanan tangkap unggulan di Gugus Pulau VIII Kepulauan Kei, secara finansial layak dilaksanakan. Kata Kunci : Komoditas unggulan, perikanan tangkap, Gugus Pulau VIII